KNOWLEDGE THAT CARES, BONDS THAT STRENGTHEN: THERAPEUTIC PLANTS IN FAMILY PRACTICES AS A CULTURAL AND IDENTITY EXPRESSION (REMUNOM, 2026)
This study describes the role of therapeutic plants in family health care practices, presenting them as cultural expressions of identity and affect transmitted between generations. The research adopted a qualitative approach, collecting information through group discussions, a multimedia diary, workshops, and interviews. The accounts presented show memories about the daily uses and meanings attributed to plants from a therapeutic and nutritional perspective. The data were analyzed using Geertz's interpretive analysis as a dense dialogical and interpretive construction, allowing the identification of how knowledge about plants and their uses is historically constructed in social relations and in lived experience within the family. The results show that the use of plants goes beyond the therapeutic dimension, configuring itself as a care system that involves affection, orality, coexistence, and practical learning in the family and community environment. Practices with teas, spices, and homemade preparations emerge as symbolic mediators of intergenerational bonds, strengthening the social memory and cultural identity of the participants. It is also observed that such knowledge remains active in contemporary daily life, although it undergoes processes of re-signification in the face of sociocultural transformations, urbanization, and the medicalization of care. In this sense, it is perceived that traditional knowledge associated with plants plays a central role in promoting relational care, cultural transmission, and strengthening family ties, which is relevant to health and well-being. In this sense, the study contributes to the appreciation of popular knowledge in the field of health and sociocultural relations.